El tamaño óptimo del gasto público y su incidencia en el crecimiento económico en el Ecuador, período 2000-2021. - Cajas Barba, Milton Santiago (2023)
The main objective of this research is to determine the optimal size of public spending that affects Ecuadorian economic growth in the period 2000-2021 from the study of theoretical models such as those proposed by (Barro, 1990), (Armey,1995), and (Sala-i-Martin, 2000), where they highlight public spending as a growth factor. These theoretical proposals complement the interpretation of the Armey curve that demonstrates the optimal level of public spending that can maximize long-term economic growth rates. To achieve this end, a quadratic model allows for optimizing spend using this econometric estimate's first derivative. It is demonstrated, based on the results obtained, that for the Ecuadorian case, public spending can raise growth rates beyond its average rate and, even more, its possible level if the said proportion is maintained at 30.23 % of GDP, at this size, public spending would have a more significant multiplier effect in a higher level of employment, a greater incentive for investment, which translates into long-term growth